Meningkatkan Kompetensi Guru melalui Pelatihan Model Pembelajaran Interaktif - Siti Fatimah Zahara; Andi Syahputra Harahap; Siswadi; Minta Ito Simamora (Pucuk Rebung: Jurnal Pengabdian kepada Masyarakat, 2021)
The objectives of this activity are: (1) Improving the ability of teachers to create a pleasant learning atmosphere for students. (2) Cultivating teachers to apply innovative, creative, effective, and fun learning in every activity (3) Improving teacher professional competence and pedagogy, especially in improving teacher competence through interactive learning models, the method used consists of (a) Counseling is intended to improve knowledge and understanding of innovative learning models, (b) Training, which is carried out by providing opportunities to practice accepted learning models. (c) Assistance, intended as a follow-up to this activity service. Assistance to teachers can be an advisor to problems faced in schools. Therefore, this training intends to improve teacher competence through interactive learning training as a learning medium at MAS Aliyah Tahfizil Qur’an Medan and how the competence of teachers in utilizing interactive learning models.